2018
DOI: 10.1364/boe.9.004893
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity of pseudophakic patients predicted from in-vitro measurements of intraocular lenses with different design

Abstract: The optical quality of a set of IOLs (modeling set: one monofocal and two bifocals) was assessed through focus by the area under the modulation transfer function (MTFa) metric and related to the visual acuity (VA) defocus curves of pseudophakic patients implanted with said IOLs. A non-linear relationship between the MTFa and clinical VA was obtained with an asymptotic limit found to be the best VA achievable by the patients. Two mathematical fitting functions between clinical VA and MTFa were derived with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 28 publications
(21 reference statements)
4
67
1
8
Order By: Relevance
“…Our study is limited to diffractive IOLs with either a single [18,19] or two combined [20,21] parabolic phase profiles of three different designs (trifocal ERV, trifocal apodized, and ERV) and two pupil sizes. Since MTFa has been proved to serve as preclinical metric for average visual performance [3][4][5]22], the results of this study will clarify whether EE metric can be used in a similar way.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our study is limited to diffractive IOLs with either a single [18,19] or two combined [20,21] parabolic phase profiles of three different designs (trifocal ERV, trifocal apodized, and ERV) and two pupil sizes. Since MTFa has been proved to serve as preclinical metric for average visual performance [3][4][5]22], the results of this study will clarify whether EE metric can be used in a similar way.…”
Section: Introductionmentioning
confidence: 93%
“…To calculate the MTFa for a given image vergence within the TF range, we computed first the MTF from the images of the four-slit test produced by the model eye with the IOL under study as reported elsewhere [4]. We averaged the four MTF curves in the horizontal and vertical directions and integrated the average MTF curve in the spatial frequency range from 0 to 50 cycles/mm, which turned out to be the MTFa value.…”
Section: On-bench Measurement Of Mtfa and Ee Quality Metricsmentioning
confidence: 99%
See 3 more Smart Citations